The impact of narrator age congruity on responses to a radio advertisement - Oakes, S.; North, Adrian (Routledge, 2011)
This study assessed the impact of the congruity between the actual age of the participants and the perceived age of narrator voices upon responses to a radio advertisement for a fictitious university. Attribute transfer caused by stereotypical age perceptions provided the explanation for results indicating that an incongruous (older) narrator significantly reduced perceptions of the image attractiveness of the advertised university. Likelihood of application and recall of advertisement content were revealed to be positive functions of the congruity between the actual age of the participants andthe perceived age of the narrator. Stereotype theory explained results revealing how the incongruous narrator made the university appear significantly more attractive to mature students (aged over 29). Although this study identified positive results in using congruous advertising stimuli, it acknowledges the possible benefits of incongruous stimuli (e.g. in terms of attention gain and creative communication).